Two P1B-1-ATPases of Amanita strobiliformis With Distinct Properties in Cu/Ag Transport - Beneš, Vojtěch; Leonhardt, Tereza; Sácký, Jan; Kotrba, Pavel (Frontiers in Microbiology, 2018)
As we have shown previously, the Cu and Ag concentrations in the sporocarps of Ag-hyperaccumulating Amanita strobiliformis are correlated, both metals share the same uptake system and are sequestered by the same metallothioneins intracellularly. To further improve our knowledge of the Cu and Ag handling in A. strobiliformis cells, we searched its transcriptome for the P1B-1 ATPases, recognizing Cu+ and Ag+ for transport. We identified transcripts encoding 1097-amino acid (AA) AsCRD1 and 978-AA AsCCC2, which were further subjected to functional studies in metal sensitive Saccharomyces cerevisiae. The expression of AsCRD1 conferred highly increased Cu and Ag tolerance to metal sensitive yeasts in which the functional AsCRD1:GFP (green fluorescent protein) fusion localized exclusively to the tonoplast, indicating that the AsCRD1-mediated Cu and Ag tolerance was a result of vacuolar sequestration of the metals. Increased accumulation of AsCRD1 transcripts observed in A. strobiliformis mycelium upon the treatments with Cu and Ag (8.7- and 4.5-fold in the presence of 5 μM metal, respectively) supported the notion that AsCRD1 can be involved in protection of the A. strobiliformis cells against the toxicity of both metals. Neither Cu nor Ag affected the levels of AsCCC2 transcripts. Heterologous expression of AsCCC2 in mutant yeasts did not contribute to Cu tolerance, but complemented the mutant genotype of the S. cerevisiae ccc2Δ strain. Consistent with the role of the yeast Ccc2 in the trafficking of Cu from cytoplasm to nascent proteins via post-Golgi, the GFP fluorescence in AsCCC2-expressing ccc2Δ yeasts localized among Golgi-like punctate foci within the cells. The AsCRD1- and AsCCC2-associated phenotypes were lost in yeasts expressing mutant transporter variants in which a conserved phosphorylation/dephosphorylation site was altered. Altogether, the data support the roles of AsCRD1 and AsCCC2 as genuine P1B-1-ATPases, and indicate their important functions in the removal of toxic excess of Cu and Ag from the cytoplasm and charging the endomembrane system with Cu, respectively.